Hipercalcemia maligna em diferentes tipos de neoplasia mamária canina - Ribeiro, Raquel Cunha (2010)
Hypercalcemia is one of the most important and frequent signs of paraneoplastic syndrome in humans, however, the incidence of this abnormality is unknown in Veterinary Medicine. So, this study aimed to carry out clinical and pathological evaluations and verify the occurrence of hypercalcemia in female dogs with mammary gland cancer. Twenty animals were selected and allocated in two groups: A – eight animals in early stage (stage I); B – twelve animals in advanced stage (stage IV and V). First, the dog were submitted to routine physical examination and laboratory evaluation that included hemogram, total and ionized calcium, creatinine, albumin, phosphorus, parathyroid hormone, serum activity of alkaline phosphatase (ALP) and alanine aminotransferase (ALT). After, they were surgically treated and the removed tissue were sent for histologic evaluation. The data from clinical evaluation were analyzed using frequency tables and the comparison between the proportions of variables between groups were perfiemed by Fisher’s test (nonparametric) and within groups by Chi-square test (p<0,05). The frequency of mammary gland cancer was higher in uncastred female dogs with age between 10 and 12 years. Caudal abdominal and inguinal glands were the most affected. In relation to hypercalcemia frequency, there was not significant difference (p= 34,73%) among the groups by Fisher’s test. In group B, two dogs showed hypercalcemia and primary hyperparathyroidism was diagnosed in both animals. However, there was not significant difference in hypercalcemia frequency by Chi-square test (p<0,05%). Thus, it can be concluded that hypercalcemia associated with mammary gland cancer is an uncommon condition in female dogs. However, it is necessary more studies with larger number of animals for stablishment of a consistent correlation between the development of mammary cancer and hypercalcemia in female dogs.